1999
DOI: 10.1007/s002130050828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nociceptin on alcohol intake in alcohol-preferring rats

Abstract: The present study investigated the effect of nociceptin (NC), the endogenous ligand of the opioid-like orphan receptor ORL1, on ethanol intake in genetically selected Marchigian Sardinian alcohol-preferring (msP) rats. Acute intracerebroventricular (i.c.v.) injection of 250 or 500 ng/rat of NC, just before access to 10% ethanol (offered 2 h/day), significantly increased ethanol intake. Subchronic (7 days) i.c.v. injection of 500 ng/rat of NC, given just before access to 10% ethanol (for 30 min/day), resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
107
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 18 publications
11
107
1
Order By: Relevance
“…Both approaches 'Anti-alcohol' effects of Ro 64-6198 A Kuzmin et al demonstrated that the effects of Ro 646198 are selective for the ADE. The effects of nociceptin (Ciccocioppo et al, 1999(Ciccocioppo et al, , 2004Martin-Fardon et al, 2000;Kuzmin et al, 2003) and Ro 64-6198 (present study) on alcohol intake may be mediated through several neurotransmitter systems. The dopamine (DA) and opioid systems regulating ethanol-related behaviors may be involved.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Both approaches 'Anti-alcohol' effects of Ro 64-6198 A Kuzmin et al demonstrated that the effects of Ro 646198 are selective for the ADE. The effects of nociceptin (Ciccocioppo et al, 1999(Ciccocioppo et al, , 2004Martin-Fardon et al, 2000;Kuzmin et al, 2003) and Ro 64-6198 (present study) on alcohol intake may be mediated through several neurotransmitter systems. The dopamine (DA) and opioid systems regulating ethanol-related behaviors may be involved.…”
Section: Discussionmentioning
confidence: 60%
“…This peptide also reduced the effects of footshock stress on ethanolseeking behavior (Martin-Fardon et al, 2000). In place conditioning experiments, nociceptin reduced alcoholinduced conditioned place preference and reinstatement of acquired place preference after extinction (Ciccocioppo et al, 1999;Kuzmin et al, 2003). The peptide alone did not affect place preference, suggesting that it is devoid of 'motivational' properties (Devine et al, 1996;Ciccocioppo et al, 1999;Kuzmin et al, 2003).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…N/OFQ injections significantly reduced home-cage ethanol intake in the two bottle choice and ethanol-induced conditioned place-preference paradigms (Ciccocioppo et al 1999(Ciccocioppo et al , 2002b). In addition, N/OFQ has been shown to inhibit stress-induced reinstatement of alcoholseeking behaviour in rats trained to self-administer ethanol (Martin-Fardon et al 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Intracerebroventricular injections of N/OFQ cause various behavioural e ects in rodents, including stimulation of food intake (Pomonis et al, 1996), inhibition or stimulation of spontaneous locomotion (Reinscheid et al, 1995;Florin et al, 1996), antagonism of the reinforcing properties of ethanol or morphine (Ciccocioppo et al, 1999;Murphy et al, 1999) and impairment of spatial learning (Sandin et al, 1997), among other actions. The peptide also a ects nociceptive transmission/perception, inducing either hyperalgesia (Meunier et al, 1995;Reinscheid et al, 1995) or reversal of analgesia mediated or induced by opioids Grisel et al, 1996).…”
Section: Introductionmentioning
confidence: 99%